Theoretical Aspects of Analysis of International Environmental Security - J. A. Rusakova (Vestnik MGIMO-Universiteta)
Abstract: International environmental security is a very hot contemporary issue of world politics, which in a large part defines the future of our environment. Dealing with this issue is of outmost importance since its failure will render all other issues and challenges as negligible. The article examines the theoretical aspects of solving the problem of environmental security. In particular, it analyzes the problem of negative social externalities, and the related concept of "tragedy of the commons." These problems create a fundamental obstacle to the implementation of environmental security at the global level. Traditionally, the problem of externalities in the environmental field have been approached economically, states and their manufacturers were to pay for the externalities in the form of additional taxes. However, experience shows that the economic tools of dealing with environmental security are not effective. The author suggests alternative non-economic approaches: strengthening and developing the system of permanent institutions of international negotiations on environmental security and promotion of environmental awareness. Solving the acute environmental problems is impossible without a change of the political philosophy of the ruling elites in most states.